The Effect of Concentration Variation of Ethanolic Extract from Potato Peels (Solanum tuberosum L.) on the Physical Properties and Antibacterial Activity of Gels against Propionibacterium acnes - Rashati, Dewi; Eryani, Mikhania Cristiningtyas (Universitas Ahmad Dahlan, 2018)
This research was aimed to know the effect of ptotato skins ethanolic extract variation concentration to physical properties of gel and antibacterial effect to Propionibacterium acnes. Gel were formulated in 3 formulas with potato skins concentration 50%, 60% and 705 respectivelly. The phisical properties of gel which obeserved include organoleptic, homogenity, pH, and spreadability. The results show that variation concentration of potato skins ethanolic extract has an effect to gel colour and viscosity but has not effect to form, smell, pH, and spreadability of gel. All formulas show strong inhibition power to Propionibacterium acnes.Â